CHALLENGES IN DIFFERENTIAL DIAGNOSIS OF COELIAC DISEASE AND GLUTEN INTOLERANCE IN CHILDREN - Г. Сенаторова; О. Омельченко; Т. Тесленко; Г. Муратов; Н. Орлова; К. Чатикян (Bukovynian State Medical University, 2023)
Introduction. The group of gluten-dependent diseases currently comprises 3 pathological conditions: celiac disease, non-celiac gluten intolerance and wheat allergy. Celiac disease is a chronic, immune-inflammatory disease that occurs in genetically predisposed individuals in response to exposure to the main cereal protein - gluten. It is characterised by damage to the small intestinal mucosa, leading to its atrophy with corresponding intestinal and extraintestinal clinical manifestations. The treatment is a lifelong gluten-free diet. Gluten intolerance is a condition characterised by the onset of irritable bowel syndrome-like symptoms within hours or days of eating gluten-containing foods. These symptoms disappear quickly when the consumption of gluten-containing products is stopped. The causes of gluten intolerance are amylase inhibitors, trypsin and fructans (FODMAPS), which are present in wheat and other gluten-containing and gluten-free foods. New recommendations from the European Society of Paediatrics, Gastroenterology, Hepatology and Nutrition (ESPGHAN) for the diagnosis of celiac disease in children were published in 2020. The diagnosis of gluten intolerance requires the exclusion of celiac disease and wheat allergy. The aim of the study was to determine the characteristics of the clinical course of celiac disease and gluten intolerance (analysis of intestinal and extraintestinal symptoms), serological and morphological features for differential diagnosis and management. Material and methods. Thirty children aged 9 months to 11 years were included in the study for the period 2016-2023. Distribution by gender: 13 (43.3%) boys and 17 (56.6%) girls, p=0.1391. Patients were divided into two groups according to the diagnosis of celiac disease and gluten intolerance. The study included a detailed medical history, assessment of the child's examination and physical development. Determination of titer of IgA antibodies, IgA to tissue transglutaminase (tTG-IgA), endomysial IgA (EMA-IgA), gliadin IgG, wheat IgE antibodies, endoscopy and morphological examination of duodenal mucosal biopsies. Descriptive analysis and comparison of two proportions were used. Non-parametric methods were used to test hypotheses. Logistic regression analysis using the relative risk index (RR) and its 95% confidence interval (CI). Differences in parameters were considered statistically significant when p<0.05. The study was approved by the Commission on Biomedical Ethics for Compliance with Moral and Legal Rules of Medical-Scientific Research of the Kharkiv National Medical University. It was confirmed that the research does not contradict the basic bioethical norms and complies with the main provisions of the Good Clinical Practice (1996), the Convention of the Council of Europe on Human Rights and Biomedicine (04.04.1997), the Declaration of Helsinki of the World Medical Association on the ethical principles of research involving human subjects (1964-2008), and the Order of the Ministry of Health of Ukraine No. 690 (23.09.2009) with amendments according to the Order of the Ministry of Health of Ukraine No. 523 (12.07.2012). Both parents of the patients were informed about the purpose and procedures of the research and signed the informed consent for their children's participation in this study. Statistical analysis was performed using Statistica 7.0 StatSoft Inc.1984-2004, (serial number 12255555555, USA) and MedCalc version 14.8-© 1993-2014 MedCalc Software bvba (Acacialaan 22 B-8400 Ostend, Belgium). The procedures, logic and interpretation of the statistical parameters obtained in the mathematical and statistical analysis were based on generally accepted rules of medical and biological statistics. Descriptive analysis and comparison of two proportions were used. Non-parametric methods were used to test hypotheses: Logistic regression analysis using the relative risk index (RR) and its 95% confidence interval (CI). Differences in parameters were considered statistically significant if p<0.05. Patients in the study were divided into two groups according to the diagnosis of celiac disease and gluten intolerance. The presented article is a fragment of the scientific research of the Department of Paediatrics No.1 and Neonatology of the Kharkiv National Medical University: topic "Medical and social adaptation aspects of children with somatic pathology in modern conditions"; state registration No.0120U102471. Results. 66.6% of children from the general cohort were diagnosed with celiac disease and 33.3% of children with gluten intolerance, p=0.0053. The mean age of the children with celiac disease was 8.4±1.0 years. Gender distribution of children with celiac disease - 50.0% boys, 50.0% girls, p=1.0000. The mean age of the children with gluten intolerance was 9.1±1.0 years. The gender distribution of children with gluten intolerance was 70.0% boys and 30.0% girls, p=0.0001. In 65.0% of children with celiac disease, the diagnosis was confirmed at an earlier stage than in children with gluten intolerance, p=0.0350. A family history of autoimmune pathology was found in 40% of children with celiac disease. All patients with celiac disease were seropositive for serological biomarkers. IgA to tissue transglutaminase tTG-IgA was detected in 95.0% of children with celiac disease (RR=20.4; 95% CI 1.4-307.2; p=0.0292). Diarrhoea and abdominal pain were found in 18/30 children from the general cohort (RR=0.8; 95% CI 0.4-1.4; p=0.5050), loss of appetite - in 17/30 children (RR=0.7; 95% CI 0.4-1.3; p=0. 2695), 15/30 children had constipation and poor weight gain (RR=0.7; 95% CI 0.3-1.5; p=0.4209), 14/30 children had delayed physical development and weakness (RR=0.9; 95% CI 0.4-1.9; p=0.7929). One third of the children had hyperactivity and attention deficit syndrome, sleep disturbances. All children with celiac disease had various stages of small intestinal mucosal atrophy according to the Marsh-Oberhuber classification. No atrophic changes in the small intestinal mucosa were found in children with gluten intolerance (normal structure of villi and crypts), but infiltrative changes were found in 60% of these patients (increase in intraepithelial lymphocytes). Conclusion. Comparative analysis showed no significant differences in the clinical presentation of celiac disease and gluten intolerance. Autoimmune pathology was not found in the family history of children with celiac disease, whereas it was found in 40% of patients with celiac disease. The diagnosis of gluten intolerance is made in case of exclusion of family history of autoimmune nosology; absence of autoantibodies to tissue tranglutaminase and deaminated gliadin peptides, endomysial autoantibodies, which should be determined on a gluten-containing diet, and absence of specific IgE to wheat. All children with celiac disease had various stages of atrophy of the small intestinal mucosa according to the Marsh-Oberhuber classification, whereas no atrophic changes were found in children with gluten intolerance, but 60% of patients with gluten intolerance had infiltrative changes in the small intestinal mucosa.